Proposing a sustainable strategy for the fabrication of robust anti-soiling coatings with enhanced antibacterial attributes for non-absorbent substrates - Nikolaos D Papadopoulos; Polyxeni Vourna (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2022)
In this paper, we propose a convenient methodology for fabricating a generic structure toward developing a robust, easy-to-clean transparent coating with inherent antibacterial properties for smooth, non-absorbent surfaces, such as glass and plastics. A two-step coating comprising an organopolysilazane primer and an alkoxysilane topcoat, based on positively charged quaternary ammonium silanes, is proposed. The topcoat is co-condensed with the primer to provide a hybrid structure with high wear strength even on surfaces that lack surface hydroxyl groups. Surfaces examined included glass and PMMA. The coated samples were studied in terms of abrasion resistance as well as anti-soiling and antimicrobial performance. It was found that the quaternary silane compound could covalently graft onto the primer acting both as an antibacterial, anti fungicidal, and hydrophobizing agent. The utility of amphoteric surfactants within the coating's solution was also examined. The resulting structure was transparent and exhibited pronounced self-disinfecting properties with remarkable sustainability. These attributes suggested a dual functionality of the coating, i.e., both anti-soiling and antimicrobial, thus rendering it a potential candidate for numerous industrial and commercial applications.